2001
DOI: 10.2746/042516401776249318
|View full text |Cite
|
Sign up to set email alerts
|

The mucosal humoral immune response of the horse to infective challenge and vaccination with Equine herpesvirus‐1 antigens

Abstract: Summary Equine herpesvirus‐1 (EHV‐1) remains a frequent cause of upper respiratory tract infection and abortion in horses worldwide. However, little is known about the local antibody response elicited in the upper airways of horses following exposure to EHV‐1. This study analysed the mucosal humoral immune response of weanling foals following experimental infection with virulent EHV‐1, or vaccination with either of 2 commercial vaccines. Twenty weanlings were assigned to 5 groups and were inoculated with, or v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 27 publications
1
58
2
6
Order By: Relevance
“…The immune response to EHV-4 infections remains poorly understood, which is partly caused by the lack of immunologically and/or virologically naïve natural hosts (35,64). As with other respiratory infections, mucosal antibodies and/or cell-mediated immunity may play a role in controlling EHV-4 infections (14). However, it is known that protective immune responses established after either infection or vaccination are shortlived and incomplete (60,74).…”
Section: E Quine Herpesvirus Type 4 (Ehv-4) Is a Member Of The Subfammentioning
confidence: 99%
“…The immune response to EHV-4 infections remains poorly understood, which is partly caused by the lack of immunologically and/or virologically naïve natural hosts (35,64). As with other respiratory infections, mucosal antibodies and/or cell-mediated immunity may play a role in controlling EHV-4 infections (14). However, it is known that protective immune responses established after either infection or vaccination are shortlived and incomplete (60,74).…”
Section: E Quine Herpesvirus Type 4 (Ehv-4) Is a Member Of The Subfammentioning
confidence: 99%
“…EHV-specific IgG isotyping, first performed on nasal washes in a study reported by Breathnach et al (5), has been adapted to assess the isotypes and relative abundances of EHV-1-specific antibodies in horse sera in a nonhazardous and efficient manner (13). We previously showed that an inactivated vaccine promoted an IgG3/5 response, whereas protective immunity from a modified-live preparation was IgG4/7 associated (13).…”
mentioning
confidence: 99%
“…Immune responses against EHV-1 in horses, however, are characterized by high levels of EHV-specific IgA, identified as the predominant isotype upon natural EHV-1 infection (9). In agreement with these data we found that heterologous prime-boost regimens comprising subcutaneous priming with plasmid DNA and two nasal boosts with recombinant EHV-1 or EHV-⌬ETIF induced high levels of transgene-specific sIgA in BALB/c mice, as assessed with bronchoalveolar lavage (BAL) fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Since the virus is absent in humans (40), it can be assumed that the problem of preexisting immunity should be of minor importance. Furthermore, EHV-1 infects a broad spectrum of different eukaryotic cells (50), and due to its ability to infect epithelial cells, EHV-1 challenge is characterized by strong mucosal immune responses (9). Due to these properties, EHV-1 strain RacH was selected recently as a novel vector for delivering vaccine genes into human cells (50,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation